(Dis)Believing and Belonging: Investigating the Narratives of Young British Atheists - Catto, Rebecca ca. 20./21. Jh. (Temenos, 2013)
The development and public prominence of the ‘New Atheism’ in the West, particularly the UK and USA, since the millennium has occasioned considerable growth in the study of ‘non-religion and secularity’. Such work is uncovering the variety and complexity of associated categories, different public figures, arguments and organizations involved. There has been a concomitant increase in research on youth and religion. As yet, however, little is known about young people who self-identify as atheist, though the statistics indicate that in Britain they are the cohort most likely to select ‘No religion’ in surveys. This article addresses this gap with presentation of data gathered with young British people who describe themselves as atheists. Atheism is a multifaceted identity for these young people developed over time and through experience. Disbelief in God and other non-empirical propositions such as in an afterlife and the efficacy of homeopathy and belief in progress through science, equality and freedom are central to their narratives. Hence belief is taken as central to the sociological study of atheism, but understood as formed and performed in relationships in which emotions play a key role. In the late modern context of contemporary Britain, these young people are far from amoral individualists. We employ current theorizing about the sacred to help understand respondents’ belief and value-oriented non-religious identities in context.